PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. BPR RESTU ARTHA MAKMUR KANTOR PUSAT MAJAPAHIT SEMARANG - Apriani, Wulan Retno; Rodhiyah, Rodhiyah; Hidayat, Wahyu (Jurnal Ilmu Administrasi Bisnis, 2012)
BPR Restu Artha Makmur is one of the companies that provide banking services. In order to achieve better corporate goals, management companies need to increase employee productivity. One aspect that can be done is by providing a fair and adequate compensation to all employees and providing a work environment that supports. Although the company has provided good compensation and good working environment, but employee productivity has not maximized yet. Problems in this study were decreased employee productivity seen from the employee's performance appraisal data does not match the target has accepted by the company. Research purposes to determine the effect of compensation and working environment on the productivity of employees. This type of research is explanatory research with a sample of 40 respondents taken by using saturated sampling techniques. Measurement scale with a Likert scale. Data was collected by interview using questionnaires. In the analysis of test data using simple linear regression test and multiple regression test with SPSS 16.0 program. While hypothesis testing using t and F test. The results explain that the compensation provided by corporate was enough good, work environment by corporate was enough good, and work productivity of employees was good. But there are few respondents who said that compensation and working environment that is not good. Compensation has a positive influence to work productivity of employees with a correlation coefficient of 0.683 and coefficient of determination of 46.7%, and the work environment has a positive influence to work productivity of employees with a correlation coefficient of 0.713 and coefficient of determination of 50.9%. Both compensation and work environment together have a significant influence to work productivity of employees with a correlation coefficient of 0.797 and coefficient of determination of 63.5% with the equation Y = 3.942 + 0.541X1 + 0.274X2. Conclusion, compensation and work environment have a positive effect on employee work productivity. There are few employees who claim that the application of the provision of compensation and work environment is poor. Suggestions for the company, should improve good and right providing appropriate compensation and working environment to the employees work productivity better than before.